Diagnostic performance of reticulocyte hemoglobin equivalent in assessing the iron status - Pawadee Chinudomwong (2020)
© 2020 The Authors. Journal of Clinical Laboratory Analysis published by Wiley Periodicals, Inc. Background: Measurement of reticulocyte hemoglobin equivalent (RET-He) is rapid, convenient, and cost-effective. Yet, researches on its performance in diagnosing iron deficiency with concurrent inflammation are limited. Hence, this study investigated RET-He value in various states, including inflammation, and evaluated its diagnostic performance in iron status assessment. Methods: Retrospectively, 953 clinical data and laboratory results—complete blood count, reticulocyte count, RET-He, and serum ferritin—were reviewed. Patients on iron therapy were excluded. Iron status was defined by serum ferritin as the reference method. RET-He among populations was investigated. Its diagnostic performance and optimal cutoff were determined by ROC analysis. Results: Three population groups were classified: healthy control, iron deficiency anemia (IDA), and non-ID anemia. Significantly, RET-He value in IDA was lower than that of healthy control, anemia of inflammation, and chronic kidney disease (P <.0001). Low RET-He was also observed in IDA with concomitant inflammation despite normal-to-high serum ferritin levels. No significant difference was observed between RET-He values in pure IDA and thalassemia (P =.57). ROC curve analysis revealed AUC of 0.876 (P <.0001) at cutoff 30 pg, by which IDA was discriminated with 74.2% sensitivity and 97.4% specificity. Applying cutoff ≤30 pg, IDA can be diagnosed with 96% sensitivity, 97.4% specificity, 80% PPV, and 99.6% NPV. Hence, RET-He >30 pg signifies a non-IDA state. Conclusion: In addition to convenience and cost-effectiveness, RET-He cutoff >30 pg can be potentially used to exclude IDA due to its excellent diagnostic sensitivity and specificity.